PENGARUH KOMPENSASI KEPUASAN KERJA DAN MOTIVASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PEGAWAI PPSU DI SALAH SATU KELURAHAN DAERAH JAKARTA UTARA - Muliani, Siti; Perkasa, Didin Hikmah (Lentera Ilmu Nusantara, 2023)
The main objective of this study is to determine the impact of compensation, job satisfaction, and motivation on OCB behavior among PPSU officers. This study used a quantitative descriptive causal research strategy. PPSU officers became participants in this study. The data collection method used a questionnaire based on a Likert scale. This research data analysis uses Smart-PLS (Partial Least Square) through hypothesis testing. PPSU officers at Pejagalan Urban Village Office, Penjaringan District, North Jakarta, proved that compensation, job satisfaction, and motivation have an impact on Organizational Citizenship Behavior (OCB).